A STUDY OF PERFECTIONISM AND SELF-HARM IN MEDICAL AND NURSING STUDENTS: THE MEDIATING ROLE OF PERCEIVED SOCIAL SUPPORT - Fatima, Sana; Shams, Aqsa; Saleem, Sadia; Sayyeda Taskeen Zahra, (Journal of Postgraduate Medical Institute, 2023)
Objective: To find out the mediating role of perceived social support between perfectionism and self-harm in medical and nursing students. Methodology: This Cross-sectional research design using questionnaires was conducted in the government and private medical universities of Pakistan (Lahore). The total 250 number of participants were chosen by using multi-stage sampling techniques, in which two strata were made, MBBS (145) and nursing students (105). The participants belonged to private and government sector with the age range 18-25 years. There are different characteristics of students that, these students had sense of responsibility, compassionate with their work and they are truthfulness to commitments. To determine the association, Perfectionistic Tendencies Scale (PTS), Multidimensional Perceived Social Support (MDSPSS) and Self-harm Tendencies Scales (SHTS) were used respectively. Statistical results of this research were analysed by using SPSS. Results. The findings highlighted that there was a significant positive association between perfectionism and self-harm tendencies (r=.171, p=.05) in students. Respectively, mediation analysis showed that perceived social support is significantly mediated between perfectionism and self-harm tendencies in students (B = .21, SE = .08, p< .001) Conclusion: Perceived social support act as significant shield for perfectionists to prevent from self-harm and mental health issues.